Adult Palatopharyngoplasty: Trends in Morbidity and Mortality from the NSQIP Database. (January 2021) - Gates, Christopher; Ramadan, Jad; Coutras, Steven; Carr, Michele
Objectives: Describe the postop morbidity of adults undergoing palatopharyngoplasty (PPP). Method: Adults who underwent PPP were studied using ACS-NSQIP (American College of Surgeons National Surgical Quality Improvement Program) database (2016-2017) via CPT code 42145. Analyzed outcomes included length of stay (LOS), readmission, reoperation, and postop complications. Predictive variables were age, gender, BMI, comorbidities. Results: A total of 1081 patients (73.7% male, mean age 42.0 years, range 18-79 years) were included. 95 (8.8%) were diabetic, 183 (16.9%) were smokers, 30 (2.8%) had preoperative dyspnea. 328 (30.3%) took medicine for hypertension. Concurrent procedures occurred in 646 (59.76%), 357 (33.02%) had nasal procedures, 320 (29.60%) had tonsil procedures, 66 (6.11%) had tongue procedures. Within 30 days postop, there were two (0.19%) mortalities. Complications included six wound infections, two dehiscences, four with pneumonia, two pulmonary embolisms, three myocardial infarctions, one DVT, three sepsis, one UTI, one who required CPR, and two who were ventilated for >48 hours. Five required reintubation. A total of 41 (3.79%) returned to OR for a related reason, at least 27 (65.90%) for bleeding. LOS ranged from 0 to 15 days, median 1 day. Overall 38 (3.52%) were readmitted for a related reason, 12 (31.58%) for bleeding and three (7.89%) for pain. Using a significance level of 0.002 (Bonferroni correction), LOS varied with presence of any concurrent procedure, BMI, and estimated probability of mortality and morbidity indices; readmission and reoperation had no significantly associated variables. Conclusion: PPP is associated with low frequency but significant morbidity and mortality.